2017
DOI: 10.1017/s1751731116002834
|View full text |Cite
|
Sign up to set email alerts
|

The response of weaned piglets to dietary valine and leucine

Abstract: Valine (Val) is considered to be the fifth-limiting amino acid in a maize-soyabean meal diet for pigs. Excess leucine (Leu) levels often occur in commercial diets, which may attenuate the effect of Val deficiency because of an increased oxidation of Val. The objective of the present experiment was to determine the effect of increasing concentrations of Leu on the response of young piglets to dietary Val. In all, 75 Large White × Landrace entire male pigs, 44 days of age and with a mean starting weight of 13.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Our equations for ADG and G:F suggest that ADFI is reduced in high Leu diets. Other research also suggests that ADFI is decreased when pigs are fed diets with high Leu or imbalanced BCAA concentrations (Harper et al, 1984;Gloaguen et al, 2011;Millet et al, 2015;Wessels et al, 2016a;Meyer et al, 2017). A possible explanation for this response is the excessive stimulation of the mammalian target for rapamycin (mTOR), a signaling pathway that stimulates protein synthesis and cell growth in the presence of adequate nutrients (Schmelze and Hall, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Our equations for ADG and G:F suggest that ADFI is reduced in high Leu diets. Other research also suggests that ADFI is decreased when pigs are fed diets with high Leu or imbalanced BCAA concentrations (Harper et al, 1984;Gloaguen et al, 2011;Millet et al, 2015;Wessels et al, 2016a;Meyer et al, 2017). A possible explanation for this response is the excessive stimulation of the mammalian target for rapamycin (mTOR), a signaling pathway that stimulates protein synthesis and cell growth in the presence of adequate nutrients (Schmelze and Hall, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Millet et al (2015) observed that growing pigs fed increasing levels of Leu had decreased growth and feed intake; however, this was able to be partially recovered by increasing the Val:Leu ratio. Similarly, a Val titration study with weaned pigs observed more severe feed intake reductions when Val:Leu ratios decreased ( Meyer et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…A reduction of ADFI was seen in diets that were deficient in Val [ 8 , 10 ], but also in Ile deficient diets [ 9 ]. Excess Leu in combination with a low level of Val in the diet had a negative impact on feed intake and consequently on the performance of piglets [ 26 , 27 ]. BCAAs get degraded by the same enzyme system complexes; thus, excess Leu may affect the requirements of Val and Ile [ 12 ] because excess Leu activates the degradation of Val and Ile too.…”
Section: Discussionmentioning
confidence: 99%